High‐Performance 2D C‐Axis‐Aligned Crystalline Oxide Semiconductor Heterostructure Transistors via Aqueous Solution Deposition - Wangying Xu; Junling Zhou; Jierui Lin; Chen Wu; Yanwei Li; Shuqiong Lan (Advanced Electronic Materials)
Abstract 2D wide bandgap oxide semiconductors with sub‐5 nm thickness have recently attracted tremendous attention owing to their unique electronic characteristics. Particularly, they can be used as promising channel materials for back‐end‐of‐line monolithic 3D integration. However, achieving both high‐mobility and high‐stability in ultrathin 2D oxide semiconductor transistors is challenging. Here, a 2D c‐axis‐aligned crystalline oxide semiconductor heterostructure strategy is proposed to overcome the mobility‐stability trade‐off in ultrathin metal oxide transistors. The 3.9 nm‐thick c‐axis‐aligned crystalline In2O3/InSmO heterostructure transistors are fabricated by cost‐effective aqueous solution deposition, showing simultaneously excellent electrical performance (mobility of 38.6 ± 0.5 cm2 V−1 s−1, on/off ratio of ≈107, and threshold voltage 1.6 ± 0.3 V) and well‐behaved bias stress stability, marked improvement over single‐layer semiconductor channel. The exceptional level of performance is attributed to the growth of highly c‐axis‐aligned crystalline structure with atomically smooth nature, the formation of quasi‐2D electron gas at the In2O3/InSmO interface, and the self‐passivation of back‐channel defect states.